Bond strength between deformed steel reinforcement bar and fibre reinforced grout - Muhamad Shafiq Annas Sapri, 1994-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017